Personality Influences the Relationship Between Primary Emotions and Religious/Spiritual Well-Being - Hiebler-Ragger, Michaela; Fuchshuber, Jürgen; Dröscher, Heidrun; Vajda, Christian; Fink, Andreas; Unterrainer, Human F. (Frontiers in Psychology, 2018)
The study of human emotions and personality provides valuable insights into the parameters of mental health and well-being. Affective neuroscience proposes that several levels of emotions – ranging from primary ones such as LUST or FEAR up to higher emotions such as spirituality – interact on a neural level. The present study aimed to further explore this theory. Furthermore, we hypothesized that personality – formed by bottom-up primary emotions and cortical top-down regulation – might act as a link between primary emotions and religious/spiritual well-being. A total sample of 167 (78% female) student participants completed the Affective Neuroscience Personality Scale (primary emotions), the Big Five Personality Inventory and the Multidimensional Inventory of Religious/Spiritual Well-Being (higher emotions). Correlation analyses confirmed the link between primary and higher emotions as well as their relation to personality. Further regression analyses indicated that personality dimensions mediate the relationship between primary and higher emotions. A substantial interaction between primary emotions, personality dimensions, and religious/spiritual well-being could be confirmed. From a developmental perspective, cortical top-down regulation might influence religious/spiritual well-being by forming relevant personality dimensions. Hence, CARE as well as Agreeableness seem of special importance. Future studies might focus on implications for clinical groups.